THE LAW OF TRANSACTIONS OF VIRTUAL LAND SALE AND PURCHASE IN METAVERSE FROM PERSPECTIVE OF FIQH MU’AMALAH - Alifia, Alya Nur (JOURNAL OF INDONESIAN COMPARATIVE OF SYARIAH LAW, 2023)
ABSTRACT            One of the modern lifestyles that is starting to spread in society is individual consumption of the Metaverse digital world. Something interesting about the Metaverse is the virtual land that owned by users can be profitable when sold, rented and invested so that users can potentially profit from price increases. In addition, Metaverse runs on blockchain technology and cryptocurrencies, which in turn can provide a truly free market.            But behind all the tempting advantages, virtual land sale and purchase transactions still has not received legal status in Islam. Because there are still immature virtual land properties to be used as an object of sale and purchase. Likewise with the crypto used for transactions. Therefore, by using a qualitative method, the researcher discusses the law of buying and selling virtual land in the Metaverse by examining binding laws on the Fiqh Mu'amalah contained in the primary data to analyze the transaction law for virtual land buying and selling transactions in the Metaverse.            The findings of this study indicate that crypto, the currency used for transactions on the Metaverse platform, does not fulfill the requirements as a currency or commodity to be traded in Islam. This is because crypto is volatile and has no supporting assets. And also regarding virtual land as an object of sale and purchase, there is an element of maysir in the transaction because the price of land depends solely on luck which is influenced by the fluctuations in the value of cryptocurrencies in circulation. Apart from that, virtual land in the form of NFT is also gharar because it cannot be presented in real terms.            The researcher hopes that this research can become a reference for Islamic law in the discussion of Fiqh Mu'amalah. And the researcher hopes that further researchers can perfect the deficiencies contained in this discussion.      Keywords : Virtual Land, Metaverse, Crypto, Sale and Purchase, Fiqh Mu’amalah